Barriers and supports for Indigenous youth and young adults with childhood- onset chronic health conditions transitioning from pediatric to adult healthcare: a qualitative study - Andrew S. Mackie; Mandi Gray; Alyssa Chappell; Kira Dlusskaya; Rick Lightning; Larry Listener; Arrol Crier; Barbara Dumigan-Jackson; Audrey Thomas; Bonny Graham; Randy Littlechild; Joshua Lightning; et al. (International Journal for Equity in Health)
Abstract Background This study examined the experiences of Indigenous youth and young adults with pediatric onset chronic health conditions who had or were about to transition from pediatric to adult healthcare services. Transition is the process by which youth develop the knowledge and self-management skills needed to manage their health condition, ideally beginning around age 12–13 and continuing until the mid-20s. There is a growing body of literature on healthcare transition, but there is an absence of literature on Indigenous youth, who face additional barriers to accessing healthcare relative to non-Indigenous Canadians. The primary objective of this study was to identify the supports and barriers for Indigenous youth with childhood-onset chronic health conditions transitioning from pediatric to adult healthcare services. Methods The research was done in the province of Alberta, Canada, in collaboration with a Community Advisory Committee comprised of Indigenous healthcare providers, Elders and Knowledge Keepers and guided by a community-based participatory research approach. Semi-structured qualitative interviews (n = 46) were conducted with Indigenous youth, caregivers, and healthcare providers. There were three Talking Circles, two for youth (9 participants) and one for caregivers (6 participants). Three research assistants coded the transcripts thematically using NVivo. The key findings were presented to the Community Advisory Committee for feedback to validate the interpretation of the qualitative data. Results The thematic findings include: (1) systemic inequalities exacerbate gaps in healthcare; (2) intergenerational trauma created unique barriers for Indigenous youth; (3) long-term relationships with care providers as a protective factor; (4) the incorporation of Indigenous worldviews into healthcare services to aid transition; and (5) assuming new responsibilities as an adult. The participants provided recommendations to improve healthcare service delivery including the need for Indigenous transition supports in community and improving education for healthcare practitioners about transition and Indigenous worldviews. Conclusion This study demonstrates the complexity of the transition experience for Indigenous youth with pediatric onset chronic health conditions. The identified barriers to successful transition could be addressed through systems level changes and the development of Indigenous specific transition support services. Such approaches need to be Indigenous-led and incorporate Indigenous culture, language, and teachings.